Pooled safety analysis of baricitinib in adult patients with atopic dermatitis from 8 randomized clinical trials. (6th October 2020) - Bieber, T.; Thyssen, J.P.; Reich, K.; Simpson, E.L.; Katoh, N.; Torrelo, A.; De Bruin‐Weller, M.; Thaci, D.; Bissonnette, R.; Gooderham, M.; Weisman, J.; Nunes, F.; et al.
Abstract: Background: Janus kinase (JAK) inhibition is a new mode of action in atopic dermatitis (AD); clarity about drug class safety considerations in the context of AD is important. Baricitinib, an oral, reversible, selective inhibitor of JAK1/JAK2, is in late‐stage development for adult patients with moderate‐to‐severe AD. Objective: To report pooled safety data for baricitinib in patients with moderate‐to‐severe AD in the clinical development program including long‐term extension (LTE) studies. Methods: This analysis included patient‐level safety data from six double‐blinded, randomized, placebo‐controlled studies (one phase 2 and five phase 3), one double‐blinded, randomized, LTE study and one open‐label LTE study, reported in three data sets: placebo‐controlled, 2‐mg – 4‐mg extended and All‐bari AD. Safety outcomes include treatment‐emergent adverse events, adverse events of special interest and abnormal laboratory changes. Proportions of patients with events and incidence rates were calculated. Results: Data were collected for 2531 patients who were given baricitinib for 2247 patient‐years (median duration 310 days). The frequency of serious infections, opportunistic infections and conjunctival disorders was low and similar between treatment groups in the placebo‐controlled period. The most common serious infections were eczema herpeticum [ n = 11, incidence rates (IR) = 0.5], cellulitis ( n = 6, IR = 0.3) and pneumonia ( n = 3, IR = 0.1). There were four opportunistic infections (IR = 0.2). No malignancies, gastrointestinal perforations, positively adjudicated cardiovascular events or tuberculosis were reported in the placebo‐controlled period in baricitinib‐treated patients. Frequency of herpes simplex was higher in the 4‐mg group (6.1%) vs. the 2‐mg (3.6%) and placebo group (2.7%); IRs in the extended data set (2‐mg IR = 9.6; 4‐mg IR = 14.5) were lower vs. the placebo‐controlled data set (2‐mg IR = 12.4; 4‐mg IR = 21.3). In the All‐bari AD data set, there were two positively adjudicated major adverse cardiovascular events (2‐mg group): two venous thrombosis events (4‐mg group) and one death. Conclusion: This integrated safety analysis in patients with moderate‐to‐severe AD confirms the established safety profile of baricitinib.